Resistance to Enneothrips flavens Moulton and genetic parameters estimation in interspecific genotypes of peanut - Pirotta, Melina Zacarelli [UNESP]; Silva, Fabiana Mota da [UNESP]; Michelotto, Marcos Doniseti; Favero, Alessandra Pereira; Godoy, Ignacio Jose de; Uneda-Trevisoli, Sandra Helena [UNESP] (Univ Estadual Maringa, Pro-reitoria Pesquisa Pos-graduacao, 2017)
Peanut is an oilseed crop of great importance for Brazilian agribusiness. A major factor affecting its production is pest incidence, mainly thrips. This study aimed to evaluate the potential for resistance to Enneothrips flavens in genotypes derived from the cross between IAC 503 and the amphidiploid (A. magna x A. cardenasii)(4x) and to estimate the genetic and phenotype parameters in these genotypes, allowing for better targeting in the selection. The experiments were conducted in a Federer augmented block design with additional checks in two generations (F-3 and F-4). Resistance to thrips was evaluated by its natural infestation and the symptoms of attacks by the insect. They were also evaluated using agronomic trait indicators of interspecific segregating with cultivated species. The results indicated that the selected progeny exhibited high resistance to thrips compared to commercial genotypes, and they had the amphidiploid as the insect resistance source. Some progenies selected as resistant also had good production traits, but with the degree of suitability to the A. hypogaea L. genotypes still low, the use of a backcross as an alternative for the introgression of resistance genes and the consequent recovery of adapted genotypes of superior recurring parents is suggested.
Keywords: Arachis hypogaea L.; thrips; resistance to insects; REML/BLUP